Delaying Food Crisis Through Reaching The Optimum Equilibrium Of The Confined Aquifer In Arid Climate Areas In Development Countries, Case Study; Area One, South Western Desert, Egypt - Gamal H. El Saeed, Neveen B. Abdelmageed, Peter Riad, Mohamed Hamdy ElKomy (International Journal of Advanced Science and Technology, 2020)
Darb El-Arbeain area lies between long. 29o 00/ and 31o 00/ E and lat. 22o 00/ and 24o 30/ N. It is divided into three separate areas; The northern part extends 90 km to the south from Paris town and has an area of 90 km2. In this study area the ground surface slopes gently from NW to SE and is characterized by a low gradient. The rainfall rarely exceeds 1 mm / year and the maximum temperature exceed 40 oC at summer and 30 oC at winter while, the minimum temperature ranges from 15 to 18 oC at midnight. In this study the hydraulic parameters scenarios of pumping rates have been explored to fit with the Egyptian ministry of irrigation using the three dimensional finite difference flow model (MODFLOW 2005) to simulate the flow system. These scenarios include: first, model will run with abstraction from the aquifers equal 1.1, 1.8, 2.8, and 3.7 of calculated initial recharge. Results indicate that the second scenario has optimum effects on the area development through optimizing the induced hydraulic parameters in the confined aquifer. To control the food crisis, it must be based on optimizing the hydraulic parameters in the confined aquifer as the groundwater is the sole source of water in that arid area.